The Influence of Scaffolding Strategy on the Reading Ability of Students: A Study on Teaching and Learning Strategy - Karsini, Karsini; Saputri, Vike Aprilianin Marwintaria; Ardianto, Hendri; Pembangunan, Heldy Ramadhan Putra (Journal of Education, Religious, and Instructions (JoERI), 2024)
This study aims to determine the influence of scaffolding strategies on students' reading ability. The problem at school is that students have difficulty understanding the text they read. Then, students are unable to conclude the content of the reading that has been read. This research uses a quantitative approach with a survey method. The population in this study is 132, with 99 samples obtained using a proportional random sampling technique. This research was conducted in schools with student respondents in the 2023/2024 Academic Year. The results of the study showed that there was a positive and significant influence between scaffolding strategies and students' reading ability.